Growth, physiological, and temperature characteristics in chinese cabbage pakchoi as affected by Cd- stressed conditions and identifying its main controlling factors using PLS model - Lantao Li; Binglin Guo; Chenchen Feng; Haitao Liu; Di Lin (BMC Plant Biology, 2022)
Abstract Background Although hormesis induced by heavy metals is a well-known phenomenon, the involved biological mechanisms are not fully understood. Cadmium (Cd) is a prevalent heavy metal in the environment. Exposure of Cd, via intake or consumption of Cd-contaminated air or food, poses a huge threat to human health. Chinese cabbage pakchoi (Brassica chinensis L.) is widely planted and consumed as a popular vegetable in China. Therefore, studying the response of Chinese cabbage pakchoi to Cd- stressed conditions is critical to assess whether cabbage can accumulate Cd and serve as an important Cd exposure pathway to human beings. In this study, we investigated the influence of Cd stress on growth, photosynthetic physiology, antioxidant enzyme activities, nutritional quality, anatomical structure, and canopy temperature in Chinese cabbage pakchoi. A partial least squares (PLS) model was used to quantify the relationship between physical and chemical indicators with Cd accumulation in cabbage, and identify the main controlling factors. Results Results showed that Cd stress significantly inhibited cabbage’s growth and development. When Cd stress was increased, the phenotypic indicators were significantly reduced. Meanwhile, Cd stress significantly enhanced the oxidative stress response of cabbage, such as the activities of catalase (CAT), superoxide dismutase (SOD), peroxidase (POD), ascorbate peroxidase (APX), and the content of malondialdehyde (MDA) in leaves. Such a change tended to increase fenestrated tissues’ thickness but decrease the thickness of leaf and spongy tissues. Moreover, Cd stress significantly increased soluble sugar, protein, and vitamin C contents in leaves as well as the temperature in the plant canopy. The PLS model analysis showed that the studied phenotypic and physicochemical indicators had good relationships with Cd accumulation in roots, shoots, and the whole plant of cabbage, with high coefficient of determination (R2) values of 0.891, 0.811, and 0.845, and low relative percent deviation (RPD) values of 3.052, 2.317, and 2.557, respectively. Furthermore, through analyzing each parameter’s variable importance for projection (VIP) value, the SOD activity was identified as a key factor for indicating Cd accumulation in cabbage. Meanwhile, the effects of CAT on Cd accumulation in cabbage and the canopy mean temperature were also high. Conclusion Cd stress has significant inhibitory effects and can cause damage cabbage’s growth and development, and the SOD activity may serve as a key factor to indicate Cd uptake and accumulation in cabbage.